2020
DOI: 10.1097/ico.0000000000002490
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Corneal Perforation in a Patient Under Anti-PD1 Therapy

Abstract: Immune checkpoint inhibition has improved the clinical outcomes for numerous patients with cancer. However, the downside is a whole new spectrum of immune-related adverse events. We report a 68-year-old man with a history of nonsmall cell lung cancer presenting with a spontaneous corneal perforation in the right eye after 22 cycles of pembrolizumab. In addition, a chronic central nonhealing epithelial defect developed after performing a penetrating keratoplasty. Treatment with autologous serum drops resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…There have only been a few similar reports of ocular toxicities, most involving corneal ulceration . One described bilateral corneal perforation in a patient taking pembrolizumab, and the other reported corneal ulceration associated with nivolimumab . Similar to the patient in this case report, these diagnoses were also made based on the association with immunotherapy and symptoms, along with pan-negative diagnostic evaluation .…”
Section: Discussionsupporting
confidence: 62%
“…There have only been a few similar reports of ocular toxicities, most involving corneal ulceration . One described bilateral corneal perforation in a patient taking pembrolizumab, and the other reported corneal ulceration associated with nivolimumab . Similar to the patient in this case report, these diagnoses were also made based on the association with immunotherapy and symptoms, along with pan-negative diagnostic evaluation .…”
Section: Discussionsupporting
confidence: 62%
“…A systematic review showed that the incidence of DED related to the use of ICIs ranges from 1.2% to 24.2% [ 199 ] The fact that these values vary widely, is consistent with our hypothesis that DED is not always reported consistently. Nevertheless, the impact on the quality of life of the patient can be important and severe DED can eventually progress to corneal perforation [ 159 , 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dry eye and corneal perforation have also been associated with the down regulation of PD-L1 [69]. Downregulation of corneal PD-L1 amplifies dry eye-associated corneal inflammation and epitheliopathy by modulating the expression of chemokine gene transcripts, which facilitates T-cell infiltration into the cornea in dry eye disease [70].…”
Section: Examples Of Disruption Of Ocular Immune Privilegementioning
confidence: 99%